Cervical Cancer Recurrence and Patient Survival After Radical Hysterectomy Followed by Either Adjuvant Chemotherapy or Adjuvant Radiotherapy With Optional Concurrent Chemotherapy: A Systematic Review and Meta-Analysis - Zhang, Yu-fei; Fan, Yu; Zhang, Peng; Ruan, Jia-ying; Mu, Yi; Li, Jin-ke (Frontiers in Oncology, 2022)
Objective: To compare cervical cancer recurrence and patient survival after radical hysterectomy followed by either adjuvant chemotherapy (AC) or adjuvant radiotherapy with or without concurrent chemotherapy (AR/CCRT). Methods: We systematically searched PubMed, EMBASE, the Cochrane Library and clinicaltrials.gov to identify studies reporting recurrence or survival of cervical cancer patients who received AC or AR/CCRT after radical hysterectomy. Data were meta-analyzed using a random-effects model, and heterogeneity was evaluated using the I2 test. Subgroup and sensitivity analyses were performed to identify potential sources of heterogeneity. Results: The meta-analysis included 14 non-randomized studies and two randomized controlled trials, altogether involving 5,052 cervical cancer patients. AC and AR/CCRT groups did not differ significantly in rates of total or local recurrence or mortality. Nevertheless, AC was associated with significantly lower risk of distant recurrence [odds ratio (OR) 0.67, 95% confidence interval (CI) 0.55-0.81] and higher rates of overall survival [hazard ratio (HR) 0.69, 95%CI 0.54-0.85] and disease-free survival rate (HR 0.77, 95%CI 0.62-0.92). Conclusions: AC may be an effective alternative to AR/CCRT for cervical cancer patients after radical hysterectomy, especially younger women who wish to preserve their ovaries and protect them from radiation damage.